A new genus for pericera septemspinosa stimpson, 1871 and pericera heptacantha bell, 1836 (crustacea, brachyura, majoidea), based on morphology and molecular data - Colavite, Jessica [UNESP]; Windsor, Amanda M.; Santana, William [UNESP] (Pensoft Publishers, 2020)
A new genus of majoid spider crab, Pohleus gen. nov. is established for Pericera septemspinosa Stimpson, 1871 and Pericera heptacantha Bell, 1836, based on morphology and molecular data from the partial sequences of the 12S and 16S mitochondrial genes and the 18S small subunit rRNA nuclear locus. The species are re-described and illustrated, based on material from several localities of the western Atlantic and eastern Pacific oceans. The carapace, antennal and pterygostomial spines, male thoracic sternum and first gonopods are distinctive characters, distinguishing Pohleus gen. nov. from species assigned to Macrocoeloma Miers, 1879, where P. septemspinosus and P. heptacanthus are currently included.
Keywords: Eastern Pacific; Epialtidae; Macrocoeloma heptacanthum; Macrocoeloma septemspinosum; Pisidae; Western Atlantic